The impact of age on the customers buying behaviour and attitude to price - Marie Slabá (Littera Scripta, 2020)
Understanding consumer buying behaviour is a crucial element of any business activities. In a marketing-oriented economy, consumer buying behaviour represents a very significant factor in business success. Therefore, there are many studies, researches and papers focusing on this phenomenon. Many different factors and characteristics have a positive or negative impact on consumer buying behaviour. Studying and understanding these factors contributes to a better understanding of consumer behaviour. Personal and socio-demographic characteristics like age, lifestyle, occupation, and many other significantly influence consumer buying behaviour. This article focus especially on age as a significant factor influencing consumer buying behaviour and customer attitude to price. For the statistical analysis of the impact of the age on consumer behaviour, one-way ANOVA will be used. Stated hypotheses on attitude to branded and non-branded goods will be analysed by chi-squared test.